Psychology for dummies - Cash, Adam. (Hoboken, NJ : Wiley Pub., 2002)
Cash includes information on what a psychologist does, how we develop intelectually, and various aspects of social, abnormal and forensic psychology.
Includes index.
1 2
Keywords: Psychology